1986
DOI: 10.1002/qua.560300307
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio scf and Ci study of the electronic structure of the trichlorine radical

Abstract: Ab initio SCF and CI calculations using a double-zeta plus polarization basis set have been canied out on the hichlorine radical CI3 to determine its electronic structure. The minimum in energy is determined for a bent structure at a bond angle of 146" and bond lengths of 2.18 8, (SCF) or 2.22 A (a). At linear geometry a *nu state is found to be lowest, approximately 7 kcal above the bent minimum, followed by a 'nl state, which is around 4 kcal higher. This situation suggests that already for low quantum numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The mechanism would then be that initial excitation populates an excited vibronic level that reemits mostly at short wavelengths. (Ab-initio calculations predict a substantial increase in the bond angle on electronic excitation. ,, ) Vibrational relaxation populates levels that emit to longer wavelengths, owing to the changes in the Franck−Condon factors (e.g., transitions to excited bending vibrational levels of the ground state become more favorable). Hence, the decay of the long wavelength emission would be artificially slowed by the collisional modification of the fluorescence spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism would then be that initial excitation populates an excited vibronic level that reemits mostly at short wavelengths. (Ab-initio calculations predict a substantial increase in the bond angle on electronic excitation. ,, ) Vibrational relaxation populates levels that emit to longer wavelengths, owing to the changes in the Franck−Condon factors (e.g., transitions to excited bending vibrational levels of the ground state become more favorable). Hence, the decay of the long wavelength emission would be artificially slowed by the collisional modification of the fluorescence spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Following this work, Wright et al suggested that a 370−420 nm emission band, observed when Cl 2 was photodissociated under relatively high-pressure conditions, might also originate from Cl 3 . In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio , and semiempirical methods. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation